28th International Symposium on Shock Waves Vol 2 - Kontis, Konstantinos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The University of Manchester hosted the 28th International Symposium on Shock Waves between 17 and 22 July 2011. The International Symposium on Shock Waves first took place in 1957 in Boston and has since become an internationally acclaimed series of meetings for the wider Shock Wave Community. The ISSW28 focused on the following areas: Blast Waves, Chemically Reacting Flows, Dense Gases and Rarefied Flows, Detonation and Combustion, Diagnostics, Facilities, Flow Visualisation, Hypersonic Flow, Ignition, Impact and Compaction, Multiphase Flow, Nozzle Flow, Numerical Methods, Propulsion, Richtmyer-Meshkov, Shockwave Boundary Layer Interaction, Shock Propagation and Reflection, Shock Vortex Interaction, Shockwave Phenomena and Applications, as well as Medical and Biological Applications. The two Volumes contain the papers presented at the symposium and serve as a reference for the participants of the ISSW 28 and individuals interested in these fields.
Part XII Multiphase Flow -- Part XIII Nozzle Flow -- Part XIV Numerical Methods -- Part XVI Propulsion -- Part XVII Richtmyer-Meshkov -- Part XVIII Shockwave Boundary Layer Interaction -- Part XIX Shock Propagation and Reflection -- Part XX Shock Vortex Interaction -- Part XXI Shockwave Phenomena and Applications -- Part XXII Special Session Medical and Biological Applications -- Part XXIII Special Session Shockwave Moderation -- Part XXIV Student Competition.
Keywords: Engineering; Hydraulic engineering; Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics; Fluid- and Aerodynamics